2015
DOI: 10.1038/ncomms7376
|View full text |Cite
|
Sign up to set email alerts
|

Bird–flower visitation networks in the Galápagos unveil a widespread interaction release

Abstract: Owing to food scarcity and to the high densities that vertebrates often reach on islands, typical insect-and seed-eaters widen their feeding niche and interact with a greater fraction of species than their mainland counterparts. This phenomenon, coined here 'interaction release', has been previously reported for single species but never for an entire community. During 4 years, we gathered data on bird-flower visitation on 12 Galápagos islands. We show that all sampled land birds exploit floral resources and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 40 publications
8
111
0
Order By: Relevance
“…Yet, despite their time investment, Chacoff et al (2012) estimate that a five-fold increase in sample effort would be needed to even possibly detect 90% of the possible interactions. The sampling effort invested in our study (190 h) spread over multiple years matches or exceeds many other studies in bird–flowering plant networks (e.g., Rodriguez-Flores, Stiles & Arizmendi, 2012; Ortiz-Pulido et al, 2012; Maruyama et al, 2014), but is considerably less than Traveset et al (2015) and studies that use video-cameras to record interactions (Maglianesi et al, 2014; Vizentin-Bugoni, Maruyama & Sazima, 2014; Vizentin-Bugoni et al, 2016). The use of remote technology in flowering plant observational studies hold much promise, but are nonetheless, difficult or expensive to use in sites where flowering plant diversity is high.…”
Section: Discussionsupporting
confidence: 58%
“…Yet, despite their time investment, Chacoff et al (2012) estimate that a five-fold increase in sample effort would be needed to even possibly detect 90% of the possible interactions. The sampling effort invested in our study (190 h) spread over multiple years matches or exceeds many other studies in bird–flowering plant networks (e.g., Rodriguez-Flores, Stiles & Arizmendi, 2012; Ortiz-Pulido et al, 2012; Maruyama et al, 2014), but is considerably less than Traveset et al (2015) and studies that use video-cameras to record interactions (Maglianesi et al, 2014; Vizentin-Bugoni, Maruyama & Sazima, 2014; Vizentin-Bugoni et al, 2016). The use of remote technology in flowering plant observational studies hold much promise, but are nonetheless, difficult or expensive to use in sites where flowering plant diversity is high.…”
Section: Discussionsupporting
confidence: 58%
“…The incorporation of R. niveus into the species' diet in less than two decades is another example of the flexibility of Darwin's Finches in exploiting newly available food sources (Tebbich et al 2004(Tebbich et al , 2008Christensen and Kleindorfer 2008). It is known that bird-flower visitation and seed dispersal networks can lead to an accelerated spread of introduced species and if so, this could be a key factor in such species becoming invasive (Richardson et al 2000;Bartuszevige and Gorchov 2006;Traveset et al 2015). As R. niveus flowers and fruits are also part of the diet of other Darwin's Finches and other land birds (Jewell and Buddenhagen 2006;Heleno et al 2013), the birds can be considered as vectors for the spread of R. niveus.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to intensively studied plant-animal interactions on the archipelago (Heleno et al 2013, Traveset et al 2015 compared to large parts of the Neotropics where tanagers are common. Whether this is primarily a true reflection of a biological pattern or due to reporting bias is difficult to determine at this point.…”
Section: Factors Determining the Distribution Of Double Mutualismsmentioning
confidence: 99%
“…Interaction release and niche expansion are common in island species; thus, island frugivores and insectivores, for instance, may often also consume other resources such as pollen or nectar (Traveset et al 2015), whereas presumed nectarivores have also been reported to feed on fruits (Spurr et al 2011). Interaction release and niche expansion are common in island species; thus, island frugivores and insectivores, for instance, may often also consume other resources such as pollen or nectar (Traveset et al 2015), whereas presumed nectarivores have also been reported to feed on fruits (Spurr et al 2011).…”
Section: Factors Determining the Distribution Of Double Mutualismsmentioning
confidence: 99%